The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1093/mtomcs/mfac025
|View full text |Cite
|
Sign up to set email alerts
|

A reliable workflow for improving nanoscale X-ray fluorescence tomographic analysis on nanoparticle-treated HeLa cells

Abstract: Scanning X-ray fluorescence (XRF) tomography provides powerful characterization capabilities in evaluating elemental distribution and differentiating their inter- and intra-cellular interactions in a three-dimensional (3D) space. Scanning XRF tomography encounters practical challenges from the sample itself, where the range of rotation angles is limited by geometric constraints, involving sample substrates or nearby features either blocking or converging into the field of view. This study aims to develop a rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…FM can be used to study the compartmentalization of surface‐modified polystyrene NPs in tissue and cell types (Kenesei et al., 2016). X‐ray tomography (XRT) is also one of the microscopic techniques used to detect and localize metal‐based NMs in combination with x‐ray fluorescence microscopy (XFM) (Luo et al., 2022). Scanning electron microscopy (SEM) is a powerful tool used for imaging the surface of samples at high magnification and resolution, providing information on the size, shape, and distribution of NPs in food (Yu et al., 2021).…”
Section: Current and New Analytical Methods And Technologies For Dete...mentioning
confidence: 99%
“…FM can be used to study the compartmentalization of surface‐modified polystyrene NPs in tissue and cell types (Kenesei et al., 2016). X‐ray tomography (XRT) is also one of the microscopic techniques used to detect and localize metal‐based NMs in combination with x‐ray fluorescence microscopy (XFM) (Luo et al., 2022). Scanning electron microscopy (SEM) is a powerful tool used for imaging the surface of samples at high magnification and resolution, providing information on the size, shape, and distribution of NPs in food (Yu et al., 2021).…”
Section: Current and New Analytical Methods And Technologies For Dete...mentioning
confidence: 99%
“…The authors appeared surprised by the data and suggested further research is urgently needed to understand the tumoral processes and associated metallomics. Luo et al 157 described the development of new procedures to improve SR-XRF tomography analysis at the nanoscale. In order to produce 3D images, the sample was rotated on the vertical axis and multiple 2D scans collected then reconstructed, but there were limitations due to angular restrictions and even the sample itself blocking regions of interest.…”
Section: Progress With Analytical Techniquesmentioning
confidence: 99%
“…Luo et al 6 demonstrated an efficient approach to expand the useable tomographic angular range making it possible to analyse local areas of interest within samples with large width-to-thickness ratios. The authors performed a sequence of XRF-CT data collections from a range of areas (micro- and nanoscale) from the same specimen.…”
Section: Chemical Imaging Using X-ray Techniquesmentioning
confidence: 99%